Writing your thesis - Oliver, Paul (SAGE study skills, 2014)
Based on his extensive experience as a successful thesis supervisor, Paul Oliver shows you how to turn your notes and data into a finished Masters or PhD thesis or dissertation. Fully up-to-date with current HEFCE/other EU requirements, the book sets out a template for you to follow, including planning and preparation, theoretical perspectives, publishing preliminary findings, and preparing for the viva.